NATIONAL DANCES AND THEIR CULTURAL HERITAGE: THE SIGNIFICANCE OF UZBEK DANCES IN FOLK CULTURE, TRADITIONAL CUSTOMS AND THEIR EXPRESSION THROUGH DANCES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The cultural heritage of Uzbek national dances forms an integral part of the people's historical, social, and spiritual values. This article examines the significance of Uzbek dances in folk culture, their connection to traditional traditions, and their role as a cultural heritage. Uzbek dances reflect such traditions as the people's way of life, respect for their spouses, wedding ceremonies, and the Navruz holiday. The article expresses opinions on the significance of dances in preserving national culture and their social role.